Implicit learning increases shot accuracy of football players when making strategic decisions during penalty kicking - Navarro, M.; van der Kamp, J.; Schor, P.; Savelsbergh, G. J. P. (Human Movement Science, 2018)
Implicit learning has been proposed to improve athletes` performance in dual-task situations. Yet, only a few studies tested this with a sports-relevant dual-task. Hence, the current study aimed to compare the effects of implicit and explicit training methods on penalty kicking performance. Twenty skilled football players were divided in two training groups and took part in a practice phase to improve kicking accuracy (i.e., without a goalkeeper) and in a post-test in order to check penalty kick performance (i.e., accuracy including a decision to kick to the side opposite the goalkeeper`s dive). Results found that the implicit and explicit training method resulted in similar levels of decision-making, but after implicit training this was achieved with higher kicking accuracy. Additionally, applications for football players and coaches are discussed. AUTORREFERAT